Activation of the Rat P2X7 Receptor by Functionally Different ATP Activation Sites - Fritz Markwardt; Malte Berthold; Sanaria Hawro Yakoob; Günther Schmalzing (Cells, 2025)
The homotrimeric P2X7 receptor (P2X7R) contains three ATP4− binding sites in its ectodomain. Here, we investigated the role of individual ATP4− activation sites in rat P2X7R (rP2X7R) using trimeric concatemers consisting of either three wild-type subunits (7-7-7) or one to three subunits with ATP binding sites knocked out by the K64A mutation. Following expression in Xenopus laevis oocytes, ATP4−-elicited ion currents were recorded using the two-microelectrode voltage clamp technique. The 7-7-7 concatamer exhibited a biphasic ATP4− concentration dependence, best fit by the sum of two Hill functions, confirming the existence of functionally distinct ATP4− activation sites. The activation time course of the 7-7-7 was best approximated by the sum of a fast and a slow exponential saturating activation component. Similarly, deactivation exhibited both fast and slow exponential decay. Only one Hill function was required to best fit the ATP4− concentration dependence of concatamers with only two or one ATP4− binding sites, and their deactivation time courses largely lacked the slowly deactivating components. We conclude that the binding of one ATP4− is sufficient for partial activation of the rP2X7R and that allosteric effects occur when all three ATP4− binding sites are occupied, leading to distinct functional activation sites.